Pengenaan Pajak Penghasilan dalam Peralihan Hak Atas Tanah Melalui Pewarisan di Kota Bukittinggi - Ikrar, Wahyul; Mirwati, Yulia; Andora, Hengki (Universitas Ekasakti, 2023)
This research aims to find out and analyze the provisions for tax imposition in the transfer of inheritance in the Bukit Tinggi City Area as well as understand and understand the income tax imposed in the inheritance process in the Bukit Tinggi City Area. This type of internal research is empirical juridical research which is carried out by researching and collecting initial data that has been obtained through direct observation of related problems. Based on the results of the author's research, BPHLTB Tax Management uses a Self-Assessment System. The tax object in BPHLTB is specifically inheritance tax as stated in Article 85 paragraph (2) letter a Law No. 28 of 2009 n Law No. 1 of 2022 concerning Financial Relations Between Regional Government and Regional Government. The basis for imposition of PPLh tax is contained in Article 2 paragraph (1) ULU PPLh, the subject of which is one of the inherited assets that has not been divided into one unit to replace those entitled to it. Meanwhile, in Article 4 Paragraph (3) ULU PPLh is excluded and one of the tax objects is inheritance.